Character Education in the Industrial Era 4.0: Optimization of al-Islam Education at SMA Muhammadiyah 2 Sidoarjo - Hazyimara, Karunia; Shabir U., Muhammad; Mardiana, Mardiana (Manajemen Pendidikan Islam STIT Palapa Nusantara, 2024)
This paper will discuss the role of Islamic religious education in schools in the formation of students' character. Character education has become a special concern in Indonesia through its integration in every subject since 2010. Moreover, Al-Islam Education that contains the values of Islamic teachings should be able to strengthen the character of students. But the reality in the field is that there is still a lot of moral degradation that occurs among students. This gap is an interesting study so that the study related to character education through the optimization of Al-Islam Education learning is present. This study uses a method in the form of a qualitative approach to field studies with the research object being at SMA Muhammadiyah 2 Sidoarjo. The data collected was obtained through interviews, observations, and data identification by reading, understanding, discussing data, presenting and drawing conclusions sourced from relevant books and journals. The results of this study show that Al-Islam Education contains the values of Islamic teachings so that it has strong relevance in shaping the character of students in the midst of the Industrial Revolution 4.0 era. The optimization of Al-Islam Education learning at SMA Muhammadiyah 2 Sidoarjo is carried out through the integration of Pancasila student profiles, the use of learning strategies that can actively involve students, teacher examples, and a supportive environment.